2016
DOI: 10.17795/jjnpp-34452
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nephroprotective Effects of Hydroalcoholic Extract of Cyperus scariosus Linn. in Gentamicin-induced Acute Kidney Injury in Wistar Albino Rats

Abstract: Background: Gentamicin is a commonly used antibiotic for the treatment of Gram-negative infections, but nephrotoxicity limits its use. Cyperus scariosus Linn. (CS) has been found to have antioxidant properties in vitro. Objectives: The aim of this study was to evaluate the nephroprotective effects of CS in gentamicin-induced acute kidney injury (AKI). Methods: The animals were divided into nine groups. AKI was produced with a 100 mg/kg intraperitoneal (i.p.) injection of gen-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In the current study, gentamicin (100 mg/kg/day) administration in albino mice displayed toxicity symptoms, as indicated by increase in serum levels of creatinine, urea, BUN, and uric acid, as well as changes in kidney cellular structure (i.e., tubular atrophy, thinning, and edema in renal parenchyma). In a study conducted by Khushboo K. et al, gentamicin 100 mg/kg/day was also shown to induce nephrotoxicity with similar symptoms [21]. Gentamicin-induced toxic effects were observed to be partially reversed in animals treated with hydroalcoholic extract of Cucumis melo seeds.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, gentamicin (100 mg/kg/day) administration in albino mice displayed toxicity symptoms, as indicated by increase in serum levels of creatinine, urea, BUN, and uric acid, as well as changes in kidney cellular structure (i.e., tubular atrophy, thinning, and edema in renal parenchyma). In a study conducted by Khushboo K. et al, gentamicin 100 mg/kg/day was also shown to induce nephrotoxicity with similar symptoms [21]. Gentamicin-induced toxic effects were observed to be partially reversed in animals treated with hydroalcoholic extract of Cucumis melo seeds.…”
Section: Discussionmentioning
confidence: 99%